Effects of Enterococcus faecalis Supplementation on Growth Performance, Hepatic Lipid Metabolism, and mRNA Expression of Lipid Metabolism Genes and Intestinal Flora in Geese - Siyu Sun; Yujie Zhao; Zhen Pang; Baoxia Wan; Jiaqi Wang; Zhenyu Wu; Qiuju Wang (Animals)
The effects of Enterococcus faecalis (E. faecalis) at a concentration of 1.0 × 108 CFU/mL on growth performance, hepatic lipid metabolism, and mRNA expression related to lipid metabolism, intestinal morphology, and intestinal flora were investigated in geese. A total of 60 male geese, aged 30 days and of similar weight, were randomly assigned to 2 groups. Each group was divided into six replicates, with five geese per replicate. During the 45-day experiment, the control group received a basal diet, while the experimental group was provided with the same basal diet supplemented with E. faecalis in drinking water at a concentration of 1.0 × 108 CFU/mL. E. faecalis significantly increased the half-eviscerated weight of geese and improved ileal intestinal morphology (p < 0.05). Serum triglyceride (TG) levels were significantly reduced on day 5, while serum total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) levels were significantly decreased on day 25 (p < 0.05). By day 45, serum TG and free fatty acid (FFA) levels were also significantly reduced (p < 0.05). Additionally, E. faecalis significantly increased the HDL/LDL ratio and serum high-density lipoprotein cholesterol (HDL-C) levels (p < 0.05). Serum insulin levels were significantly elevated on day 25, and glucagon-like peptide-1 (GLP-1) levels were significantly increased on day 45 (p < 0.05). On day 25 of the trial, hepatic TG levels, FFA levels, and Oil Red O-stained areas in the liver were significantly reduced (p < 0.05), accompanied by significantly decreased mRNA expression of hepatic acetyl-CoA carboxylase (ACCA) (p < 0.05). Conversely, the mRNA expression levels of fatty acid synthase (FASN), farnesoid X receptor (FXR), sterol regulatory element-binding protein 1 (SREBP-1), and peroxisome proliferator-activated receptor-α (PPARα) were significantly elevated (p < 0.05). A 16S rRNA diversity analysis of ileal contents on day 25 revealed significant differences in intestinal flora composition between the control and E. faecalis groups. The 16S rRNA data demonstrated a strong correlation between microbial communities and lipid-related physiological and biochemical indicators (p < 0.05). In conclusion, E. faecalis supplementation promoted fatty acid oxidation, reduced blood lipid levels, alleviated hepatic lipid accumulation, and improved ileal morphology and intestinal flora diversity, thereby enhancing growth performance and lipid metabolism in geese. These findings suggest that E. faecalis is a promising probiotic candidate for development as a feed additive.